Uncorking MCU to let the calcium flow. (November 2020) - Foskett, J. Kevin
Abstract: New cryo-electron microscopy structures of the mitochondrial Ca 2+ uniporter ion channel complex in various conformations reveal channel gating regulation by Ca 2+ -dependent unblock of the channel pore by MICU1.